A Systematic Scoping Review of the Choice Architecture Movement: Toward Understanding When and Why Nudges Work - Szaszi, Barnabas; Palinkas, Anna; Palfi, Bence; Szollosi, Aba; Aczel, Balazs (Journal of behavioral decision making, 2018)
In this paper, we provide a domain‐general scoping review of the nudge movement by reviewing 422 choice architecture interventions in 156 empirical studies. We report the distribution of the studies across countries, years, domains, subdomains of applicability, intervention types, and the moderators associated with each intervention category to review the current state of the nudge movement. Furthermore, we highlight certain characteristics of the studies and experimental and reporting practices that can hinder the accumulation of evidence in the field. Specifically, we found that 74% of the studies were mainly motivated to assess the effectiveness of the interventions in one specific setting, while only 24% of the studies focused on the exploration of moderators or underlying processes. We also observed that only 7% of the studies applied power analysis, 2% used guidelines aiming to improve the quality of reporting, no study in our database was preregistered, and the used intervention nomenclatures were non‐exhaustive and often have overlapping categories. Building on our current observations and proposed solutions from other fields, we provide directly applicable recommendations for future research to support the evidence accumulation on why and when nudges work. Copyright © 2017 John Wiley & Sons, Ltd.